Peran Konten Interaktif dalam Membangun Keterlibatan Konsumen dan Memperkuat Kesetiaan Merek: Tinjauan pada Platform Media Sosial dan Situs Web Perusahaan - Klemens Mere; Dewi Puspitasari; Muhammad Asir; Betty Rahayu; M. Imron Mas'ud (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Interactive content has become one of the primary strategies in building consumer engagement and strengthening brand loyalty in the current digital environment. This article aims to investigate the role of interactive content in this context with a focus on social media platforms and corporate websites. The literature review method is employed to analyze various studies and perspectives related to this topic. Findings indicate that interactive content has a significant positive impact on consumer engagement and brand loyalty. Through active interaction between brands and consumers, stronger relationships can be built, thereby enhancing consumer loyalty to the brand. The importance of presenting engaging, relevant, and easily accessible content is also highlighted in this literature. Amidst the rapid development of technology and consumer behavior dynamics, a profound understanding of the role of interactive content becomes increasingly important for marketing practitioners. Thus, this article provides valuable insights for practitioners and researchers in designing effective content strategies to strengthen brand-consumer relationships in the digital era. Keywords: Interactive Content, Consumer Engagement, Brand Loyalty